DEVELOPMENT STRATEGY GAP IN SOCIAL POLICY - SOCIAL PROBLEM INTERACTION: APPRAISAL OF NATIONAL POVERTY ERADICATION PROGRAMME IN RURAL COMMUNITIES OF AKWA IBOM STATE, NIGERIA. - Festus, Nkpoyen; Ugo Chuks, Okolie,; Onyema, Okwu A.; , Esther P, Archibong; , Brown E, Isokon; Chimaobi, Okorie,; Fidelis Ngaji, Akwaji,; Glory, Bassey (International Journal of Psychosocial Rehabilitation, 2024)
The study investigated development strategy gap in social policy and social problem interaction by examining the impact of the social welfare policy of NAPEP on rural communities in AkwaIbom State of Nigeria. Specific objectives were to demonstrate the extent to which existing implementation gap foisted by non-participation of benefitting communities in poverty eradication programme, diversion of programme funds through corruption and non-commitment to policy execution impact on poverty reduction in rural communities. Relevant and related literature was reviewed. The human development (capability approach) was adopted as the theoretical framework. The Expost facto research design was adopted. Two local government areas (Oron and Udung Uko) constituted the study areas. Multistage sampling procedure was utilized to obtain the data using a 26-item research instrument from 400 respondents determined through the use of Taro Yamene sample size determination formula. Data were analysed using Chi-square(X2) statistical technique. Thestudy revealed that a significant association exists between non-participation of beneficiary communities in poverty eradication project design/implementation at local level and poverty reduction in rural communities; a significant relationship exists between corrupt practices and poverty reduction in rural communities, poor policy implementation strategy has a significant association with poverty reduction in rural communities. Analyses of data revealed that the calculated (x2) values of 42.46, 192.82 and 20.03 respectively were higher than the critical value of 7.81 Although NAPEP, the government intervention strategy has the potential to reduce poverty, but it has not been able to lift rural dwellers out of extreme poverty because of development gaps induced by non-inclusion of beneficiaries in program decisions, corrupt practices and poor policy implementation. Rural dwellers have not experienced the impact of NAPEP.